Mali : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1994)
This paper reviews economic developments in Mali during 1990-94. In the tertiary sector, trade continued to be the leading source of value added; its share in GDP increased continuously, from 17 percent in 1989 to 18.5 percent in 1993. This was compensated by a marked decline of the share of public administration, reflecting the containment of the wage bill and the streamlining of the civil service. The consumption share in GDP averaged a little less than 95 percent during 1989-93.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet